The global burden of group A streptococcal diseases - Carapetis, Jonathan R; Steer, Andrew C; Mulholland, E Kim; Weber, Martin (The Lancet infectious diseases, 2005)
The global burden of disease caused by group A streptococcus (GAS) is not known. We review recent population-based data to estimate the burden of GAS diseases and highlight deficiencies in the available data. We estimate that there are at least 517 000 deaths each year due to severe GAS diseases (eg, acute rheumatic fever, rheumatic heart disease, post-streptococcal glomerulonephritis, and invasive infections). The prevalence of severe GAS disease is at least 18·1 million cases, with 1·78 million new cases each year. The greatest burden is due to rheumatic heart disease, with a prevalence of at least 15·6 million cases, with 282 000 new cases and 233 000 deaths each year. The burden of invasive GAS diseases is unexpectedly high, with at least 663 000 new cases and 163 000 deaths each year. In addition, there are more than 111 million prevalent cases of GAS pyoderma, and over 616 million incident cases per year of GAS pharyngitis. Epidemiological data from developing countries for most diseases is poor. On a global scale, GAS is an important cause of morbidity and mortality. These data emphasise the need to reinforce current control strategies, develop new primary prevention strategies, and collect better data from developing countries.